Case Report: Incidental diagnosis of cystic fibrosis via whole genome sequencing alters HSCT planning in a child with cerebral X-linked adrenoleukodystrophy - Sy, Jann Adriel Chua; Tan, Poh Lin; Lin, Jeremy Bingyuan; Tay, Stacey Kiat-Hong; Chin, Hui-Lin (Frontiers in Pediatrics, 2025)
Cerebral X-linked adrenoleukodystrophy (cALD) is an X-linked peroxisomal disorder caused by pathogenic variation in the ABCD1 gene, characterized by progressive central nervous system demyelination leading to severe neurocognitive decline, as well as concomitant adrenal insufficiency resulting from fatty acid accumulation. When instituted early, haematopoietic stem cell transplantation (HSCT) can halt neurological disease progression. Whole genome sequencing can clarify the diagnosis of cALD but may also reveal conditions with significant clinical implications, as in our case. To our knowledge, this is the first published case where an incidental finding of cystic fibrosis influenced pre-HSCT workup and subsequent management in a child with cALD. A 6-year-old boy presented with subacute neuroregression, manifesting as deteriorating cognition and speech, hyperactivity, clumsiness, and swallowing dysfunction. Brain MRI confirmed symmetrical demyelinating lesions consistent with cALD, and whole genome sequencing (WGS) identified a maternally-inherited pathogenic ABCD1(NM_000033.4):c.521A>G (p.Tyr174Cys) variant. WGS also incidentally identified compound heterozygosity for two pathogenic variants in CFTR, supporting an incidental cystic fibrosis (CF) diagnosis, clinically verified by an abnormal sweat test and radiological findings of subclinical bronchiectasis, as the child was asymptomatic. This influenced the HSCT conditioning regimen prescription and reinforced the need for enhanced infectious prophylaxis and vigilant respiratory support. This case highlights the potential of comprehensive genomic approaches to reveal previously undetected comorbidities. Integrating CF management into a cALD-directed HSCT protocol mitigated peri-transplant risks, demonstrating the value of multidisciplinary care when incidental diagnoses emerge.